Alginate and Spirulina Vast-Promoting Immune Activity and Resistance to Diverse Vibrio Species in Litopenaeus vannamei Culture - Ervia Yudiati; Agus Trianto; Sarjito Sarjito; Diah Ayu Satyari Utami; Murni Karim; Nuril Azhar (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
Litopenaeus vannamei is a key species in global aquaculture; however, its susceptibility to vibriosis presents a persistent challenge. The aim of this study was to investigate the effects of dietary supplementation with alginate and Spirulina hot water extract (SWE) on the immune response and gene expression associated with pathogen resistance. Shrimp fed diets containing 3 g·kg⁻¹ of alginate and 5 mg·kg⁻¹ of SWE exhibited marked improvements in immune parameters, including total hemocyte count, phagocytic activity, phagocytic index, phenoloxidase activity, and superoxide dismutase levels, as measured on days 3 and 7 (P< 0.05). Following challenge with Vibrio parahaemolyticus, V. vulnificus, and V. harveyi, treated shrimp demonstrated a 90% survival rate compared to 0% in the control group. Gene expression analysis revealed a 2-fold and 1.5-fold upregulation of prophenoloxidase (proPO) and lipopolysaccharide β-glucan binding protein (LGBP), respectively, indicating the activation of the proPO cascade and pathogen recognition pathways. These results provide direct evidence that alginate and SWE act as immunostimulants by modulating hemocyte function and immune-related gene expression. The findings of the present study suggest that oral supplementation with these natural bioactive compounds can serve as a functional dietary strategy to enhance disease resilience in shrimp and promote more sustainable aquaculture systems, in seven days period.